2011
DOI: 10.1111/j.1365-2354.2011.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Incurable, invisible and inconclusive: watchful waiting for chronic lymphocytic leukaemia and implications for doctor-patient communication

Abstract: Patients with chronic lymphocytic leukaemia (CLL) find it hard to accept a diagnosis of an incurable cancer for which no treatment is recommended and which may not cause symptoms for many years. We used qualitative interviews with 12 people with CLL managed by watchful waiting, drawn from a maximum variation sample of 39 adults with leukaemia, to explore accounts of watchful waiting and implications for clinical management. Patients with CLL recalled being given little information about the condition and wante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…There are many studies on how to improve communication by, for example, enhancing the professional's awareness of and attentiveness to what the patient expresses (Wilkinson et al 2003;Uitterhoeve et al 2009;Lenzi et al 2011;Evans et al 2012;Udo et al 2013). Reflection may be a useful strategy in developing both personal and professional awareness and enhancing understanding (Maggs & Biley 2000;Thorpe & Barsky 2001;Gustafsson & Fagerberg 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on how to improve communication by, for example, enhancing the professional's awareness of and attentiveness to what the patient expresses (Wilkinson et al 2003;Uitterhoeve et al 2009;Lenzi et al 2011;Evans et al 2012;Udo et al 2013). Reflection may be a useful strategy in developing both personal and professional awareness and enhancing understanding (Maggs & Biley 2000;Thorpe & Barsky 2001;Gustafsson & Fagerberg 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a significant proportion of participants had been diagnosed more than two years prior to the survey, it is likely that some may have completed treatment and/or were in the ‘watchful waiting’ stage of survivorship [19]. …”
Section: Discussionmentioning
confidence: 99%
“…One group reported on 12 patients with CLL on watchful waiting that many "experience levels of depression, anxiety, and quality of life similar to those in active treatment; our qualitative approach has illuminated some of the reasons for the negative psychological impacts." 27 In a larger sample of over 400 survivors with CLL who were untreated, the investigators reported that compared with a normal population that "the greatest differences were in fatigue, sleep disturbance, role functioning, and global HRQoL." 28 Fatigue was reported by 81% of patients, compared with the next most common symptoms: sleep disturbance (56%) and dyspnea (49%).…”
Section: Chronic Survivorshipmentioning
confidence: 97%